Podejście procesowe w systemach informatycznych przedsiębiorstw - Zygała, Ryszard (The Process Approach in Business Information Systems, 2009)
The business process approach is very important for the contemporary business information systems theory and practice. Process orientation was implemented in most leading software packages. The process approach is also very popular in the software engineering theory and practice. The business process perspective determines IT domain control and management. The main goal of the article is to present the importance of the process approach for the information systems realm. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 270-278